Dividing Harm - Øverland, Gerhard (Journal of moral philosophy, 2011)
In this paper I argue that mere causal contribution to harm is morally significant on two counts: a) innocent aggressors have a duty to bear additional costs to help protect their potential victims, as compared to the duty innocent bystanders are expected to bear, and correspondingly; b) it is permissible to use more force against innocent aggressors, as used in self-defense and defense of others, than innocent bystanders. The paper has two parts. First I aim to demonstrate the intuitive plausibility of this proposal and what I call “the asymmetrical fair share procedure.” According to this procedure, innocent aggressors have a duty to take on a fair share of the harm if dividing it is possible, and a fair share of the risk of being harmed if redistribution of harm is impossible. In the second part, I develop a contractual account explaining why mere contribution is morally significant.